Optimization of Meninting Dam water utilization to meet Irrigation, Raw Water, and Micro Hydro Power Plant potential needs - Grahestika, Ni Ketut Laksmi; Setiawan, Ery; Sulistiyono, Heri (International Journal Labs, 2025)
The construction of the Meninting Dam located in West Lombok Regency, was motivated by the unequal supply of water on Lombok Island. The Meninting Dam was built with the aim of providing irrigation water to Sesaot, Penimbung, and Ketapang Irrigation Area. Apart from that, it is also to supply raw water needs and is used for electricity generation. In fulfilling these goals, it is necessary to carry out careful calculations and use water optimally in an effort to meet these needs. This research aims to obtain optimization results from water utilization with the objective function in the form of maximum profit with a decision variable in the form of optimal irrigated land area and to determine the annual benefit value from dam water use. Optimization analysis is carried out using program Solver in Microsoft Excel. In calculating water availability, Orong Atas AWLR data is used with an area comparison formula. Meanwhile, in calculating the need for irrigation water, several alternatives were tried based on the start of different planting seasons. Based on optimization calculations using Solver, the optimum area was obtained at 1065,29 ha in Sesaot Irrigation Area, 454 ha in Penimbung Irrigation Area, and 40 ha in Ketapang Irrigation Area with a planting intensity for each irrigation area of 300% and reliability of the reservoir at the November I planting season was 80,42%. The value of annual benefits obtained in one year from the productivity of paddy and secondary crops, raw water, and electricity is IDR 105.168.334.600,00.